Pengaruh Penambahan Biji Chia dan Selasih Terhidrasi terhadap Sifat Fisikokimia, Sensori, dan Mikrobiologis Yoghurt - Rahmawati, Medina Alia; Patricia, Kezia; Adawiyah, Dede Robiatul; Prangdimurti, Endang (Jurnal Teknologi dan Industri Pangan, 2024)
Chia and basil seeds are a plant-based source that possess unique characteristic, including the ability to form a gel when hydrated due to polysaccharide layer on outer seeds can absorb water This property can be applied to food products that may easily suffer texture damage such as yogurt. Therefore, further research is needed to determine the potential of chia and basil seeds as a hydrocolloid source that can affect yogurt characteristics and total lactic acid bacteria (LAB). Chia and basil seeds in this study were each processed into two treatments: flour and hydration of whole seeds (1:30). Each treatment was added to yogurt formulation with concentration: 0, 1, 2, and 3% (w/v), then evaluated by preference test to determine selected formulation. Two formulations that were organoleptically preferred by panelists were yogurt with hydrated chia 2% and hydrated basil 3% according to hedonic rating test. The selected formulations were proximate content analysis, syneresis, viscosity, and total LAB. The addition of chia and basil seeds into yoghurt had significant effects on syneresis and viscosity at a significance level of 5%. The syneresis of yogurt with hydrated chia 2% was 1.37±0.21% while the syneresis of yogurt with hydrated basil 3% was 0.58±0.05% which was lower than control 2.44±0.24%. Viscosity of yogurt with hydrated chia 2% was 3808.33±38.19 cP and yogurt with hydrated basil 3% was 4175.00±25.00 cP, which was higher than control 3116.67±28.87 cP. Total LAB in chia yogurt reaching 1.1 109 CFU/g and basil yogurt reaching 1.2 109 CFU/g was higher than control 8.7 107 CFU/g. Overall, the addition of chia and basil seeds improved the quality of yogurt.